“Geo-Archaeo-Routes” on the Island of Lemnos: The “Nalture” Experience as a Holistic Geotouristic Approach within the Geoethical Perspective - Triantaphyllou, Maria V.; Firkasis, Nikolaos; Theodora, Tsourou; Vassilakis, Emmanuel; Spyrou, Evangelos; Koukousioura, Olga; Oikonomou, Argyro; Athanasios Skentos (Geosciences, 2023)
The geosites of Lemnos represent local touristic products that, beyond their high aesthetic value, display significant scientific links to the geological past as well as prehistory and history, archaeology, mythology and religious heritage of the island. The unique wealth of Lemnos geosites in combination with the abundance of archaeological sites, cultural monuments and museums composes the basis of what we define here as “Geo-Archaeo-Routes”: certain routes that can be geographically defined, offered, guided and finally followed by the touristic masses. The outcome of the performed quantitative Lemnos geosite assessment enables decision making, thus providing a toolbox useful for sustainable Geo-Archaeo-tourism development at a local level and forms the basis for designing “Geo-Archaeo-Routes”. “Geo-Archaeo-Routes” are particularly favorable of environmentally friendly alternative types of tourism, attracting naturalists, hikers, fans of cultural or religious tourism and many others who represent a major part of the touristic needs of the 21st century. The established hiking and road “Geo-Archaeo-Routes” on Lemnos Island may represent a distinctive touristic product as they offer a high level of “nalture” entertainment, blending “nature with culture” in the framework of a holistic geotouristic approach.